Getting services for your child on the autism spectrum - Foley, Matthew G. (Jessica Kingsley, 2002)
For any parent of a child on the autism spectrum, obtaining educational and other services for their child is an ongoing and often intractable problem. This book tells the story of two parents of a child first diagnosed with Pervasive Developmental Disorder Not Otherwise Specified (PDD-NOS), whose initial experiences with the education system were not unlike those of most parents of a child with a disability. Their role soon changed from parents to parent/professionals when they realized that the professionals were not sure how to respond to their son's special needs. This book describes their.